Assesing the Role of ESG on Firm Value in Indonesia: Signaling or Symbolism? - Prasetyo, Rifki Adhi; Rissa Anandita; Nur Amaliyatun Anisa Br Ginting (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This research delves into how Environmental, Social, and Governance (ESG) disclosures affect a company’s value, using Tobin’s Q as a measure of market performance. It centers on companies included in the KOMPAS100 index of the Indonesia Stock Exchange from 2020 to 2023, applying a fixed-effects panel regression model to assess the impact of each ESG aspect using Stata. The ESG disclosure scores and firm value represented by Tobin’s Q were collected from Bloomberg Database. The findings reveal that none of the ESG elements—environmental, social, or governance—have a statistically significant influence on firm value. Although all three variables display negative but insignificant coefficients, this suggests that ESG disclosures in Indonesia are not yet perceived by investors as adding value. These results support signaling and stakeholder theories, which stress the need for reliable information and active stakeholder involvement for ESG to affect firm valuation. The study underscores the necessity for enhanced ESG transparency, stricter regulatory enforcement, and greater investor awareness in emerging markets. It also provides practical advice for companies, policymakers, and investors aiming to bolster ESG integration and reporting standards in Southeast Asia.